Generalization of one problem of stochastic geometry and related measure-valued processes - Yurachkovskii, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove a functional limit theorem for the measure of a domain in which the values of a time-dependent random field do not exceed a given level. We illustrate this theorem by a geometric model.